Tanggung Jawab Direktur yang Ultra Vires yang Menyebabkan Kepailitan Perusahaan - Bagus Ramadhan (Faculty of Law, Universitas Airlangga, 2022)
AbstractThe Board of Directors of a Limited Liability Company has the task and authority to carry out the management of the company in accordance with the company's articles of association. If the company's board of directors commits acts outside of the company's purposes and objectives and exceeds the limits of authority given by the UUPT, articles of association and gms decisions, then the actions of the board of directors can be categorized as act of ultra vires. The ultra vires doctrine is a doctrine that considers null and void of any action of the company that exceeds the authority granted as stated in the purpose and purpose of the Company. Referring to Article 97 uupt, if the board of directors performs act of ultra vires,then the board of directors must be personally responsible for the losses suffered by the company. In reality it is still difficult to hold the company's directors personally accountable. UUPT is a regulation that regulates the limitative regarding Limited Liability Companies. Uupt in principle adheres to the doctrine of ultra vires seen in the formulation of several clauses. However in the UUPT is not formulated sanctions against violations of ultra vires. Keywords: Doctrine Ultra Vires; Directors; Authority Responsibility; Company; Bankruptcy. AbstrakDireksi Perseroan Terbatas mempunyai tugas dan wewenang menjalankan pengurusan perseroan sesuai dengan anggaran dasar perseroan. Bilamana direksi perseroan melakukan perbuatan diluar dari maksud dan tujuan perseroan serta melampaui batas kewenangan yang diberikan oleh UUPT, anggaran dasar maupun keputusan RUPS, maka perbuatan direksi tersebut dapat dikategorikan sebagai act of ultra vires. Doktrin ultra vires adalah suatu doktrin yang menganggap batal demi hukum atas setiap tindakan perseroan yang melebihi kewenangan yang diberikan sebagaimana yang disebutkan dalam maksud dan tujuan perseroan. Mengacu Pasal 97 UUPT, bilamana direksi melakukan act of ultra vires, maka direksi harus bertanggung jawab secara pribadi atas kerugian yang dialami perseroan. Pada kenyataannya masih sulit meminta pertanggungjawaban secara pribadi kepada direksi perseroan yang melakukan act of ultra vires. UUPT merupakan regulasi yang mengatur limitatif mengenai Perseroan Terbatas. UUPT secara prinsip menganut doktrin ultra vires yang terlihat dalam rumusan beberapa klausul. Namun dalam UUPT tidak dirumuskan sanksi terhadap pelanggaran ultra vires. Kata Kunci: Doktrin Ultra Vires; Direktur; Tanggung Jawab; Perseroan; Kepailitan.